Pedagogic Code-Switching: A Case Study of the Language Practices of Filipino Teachers in English Language Classrooms - Mangila, Benjamin Baguio (English Language Teaching Educational Journal, 2018)
This study was conducted to primarily investigate the language practices of two bilingual Filipino teachers in English language classrooms. It made use of the qualitative case study guided by Hymes’ methodological approach of the ethnography of communication. The findings of this study revealed that teachers made use of code-switching in teaching and they code-switched for several pedagogic purposes. In sentential-level analysis, the results showed that several code-switching acts were made by teachers in classroom discourse. Intra-sentential, inter-sentential, and intra-word code-switch types were most commonly used by teachers while extra-sentential code-switch was not used in their classroom discourses. In pedagogic-functional level analysis, the results revealed that the teachers frequently used code-switching mostly for instructional or content acquisition. The findings also showed that teachers sometimes code-switched for reformulation and facilitation but they rarely code-switched for language acquisition and habitual purposes. This study recommended that a similar study be conducted to gather sufficient data on class interactions through utilizing intensive classroom observations to deepen investigation on teachers’ language practices. Furthermore, it also recommended that other methods like interviews could also be done to gather teachers’ viewpoints about when and why they code-switch and their attitudes toward their use of code-switching in second language classrooms.